Art therapy for the prevention of cognitive decline. (July 2019) - Lee, Rachael; Wong, Jonathan; Lit Shoon, Wong; Gandhi, Mihir; Lei, Feng; EH, Kua; Rawtaer, Iris; Mahendran, Rathi
Highlights: The feasibility of structured art therapy and music reminiscence activity was evaluated in a RCT with N = 68 older adults with MCI. Older adults receiving art therapy had improvements in memory and attention at 3 months, with sustained improvement in memory after 6 months. The significant improvement with art therapy, highlights the potential cognitive benefits of structured art therapy in older adults with mild cognitive impairment. Abstract: In recent years, non-pharmacological approaches have been introduced for older adults with mild cognitive impairment (MCI) in an attempt to address cognitive decline and improve cognitive functioning. Art therapy is a widely accepted psychosocial treatment known to engage attention and enhance cognition, and improve mood for persons with dementia. However, research assessing the benefits of art therapy in the MCI population is limited. This study used structured art therapy that was introduced as a 9-month randomized control trial of older adults with MCI (N = 68). The trial involved three arms, art therapy (N = 22), music reminiscence activity (N = 24) and a control group (no treatment; N = 22). Both art therapy and music reminiscence activity were conducted weekly for 3 months and then fortnightly for 6 months. Art therapy comprised of two structured components, physical creation of art pieces and the cognitive evaluation of paintings. The primary outcome, cognitive performance on neuropsychological tests, showed significant improvement in memory domains which were sustained at 9 months with art therapy. Additional improvements were noted in visuospatial abilities, attention, working memory, and executive function.